POTENSI JONGGOL GARDEN DI DESA CIBODAS DALAM PROSPEK PENGEMBANGAN EKOWISATA - Dian Meliantari (Jurnal Perspektif Manajerial dan Kewirausahaan (JPMK), 2022)
ABSTRACT The covid pandemic has devastated the Indonesian economy, including the tourism industry. After the pandemic, tourism began to reopen, one of which was Jonggol Garden which has thepotential to be developed into eco-tourism. This study aims to determine the potential and obstacles of Jonggol Garden after the pandemic. The method used is the kuantitatif method with purposive and incidental sampling through the provision of questionnaires, interviews and secondary data from literature materials. Data analysis with SWOT and Univariate and bivariate for each observed variable. The results showed that Jonggol Garden has enough potential and opportunities as an ecotourism destination near the city even though visitors are declining. Its existence is able to support the economy of the surrounding community even though it is not yet comprehensive. The weakness of Jonggol Garden is the lack of capital for the cost of repairing facilities and infrastructure. In addition, Jonggol Garden has threats from other tours that have begun to appear around it. While the results of the bivariate analysis of the Facilities and Infrastructure variables, visitor satisfaction results are not significant. Road access to tourist attractions related to Tourism Satisfaction is very significant. Moderate Cleanliness is significantly related to Tourist Attractions Keywords: post-pandemic, ecotourism, Jonggol tourism, Jonggol Garden, Creative economy.